An Environmentally Friendly Flow Injection-Gas Diffusion System Using Roselle (Hibiscus sabdariffa L.) Extract as Natural Reagent for the Photometric Determination of Sulfite in Wines - Preeyaporn Reanpang; Teerarat Pun-uam; Jaroon Jakmunee; Supada Khonyoung (Journal of Analytical Methods in Chemistry)
In this work, a green and simpler method for photometric determination of sulfite based on a flow injection-gas diffusion (FI-GD) system using a natural reagent extracted from roselle (Hibiscus sabdariffa L.) was proposed. Despite the fact that the employed reaction is not selective to sulfite, its sensitivity is high, and the selectivity can be improved by coupling a GD unit to the FI system. The method involves monitoring a decrease in absorbance of the reagent solution that is used as an acceptor solution. When a standard solution or sample solution was injected into an acidic donor stream, the liberated sulfur dioxide diffuses through a gas-permeable membrane of the GD unit into the acceptor solution, causing color fading of the reagent. A linear analytical curve in the range of 5–100 mg L−1 was obtained with a detection limit of 2 mg·L−1. Relative standard deviations of 0.9%, 0.6%, and 0.6% were obtained for the determination of 30, 70, and 100 mg·L−1 SO32- (n = 11). The developed method was applied to wine samples, giving results that agreed with those obtained with the Ripper titrimetric method. The proposed method offers advantages of simplicity, cost-effectiveness, and being environmentally friendly such as reduced chemical consumption and less waste generation.